A fast, high-throughput digital coincidence detection system for a large RPC-PET camera - Clemêncio, Filomena (2022)
Current work aiming at studying the feasibility of a resistive plate chamber (RPC)- PET camera for human whole-body screening indicates that a very cost-effective and highsensitivity camera can be built. Such a camera will use the high intrinsic time resolution (better than 300 ps full width at half maximum (FWHM) of the RPC technology to implement a time of flight (TOF)-PET camera that, along with its very large field of view, can reach a sensitivity exceeding the present crystal-based PET technology by a factor up to 20 with a spatial resolution near 2 mm. Due to the large number of RPC plates forming such a system (in the order of 100 RPC plates, or even more) and to the large amount of data generated it is essential to have an effective on-line trigger that helps reducing the pressure on the data saving and processing system. In this work we present simulation results of an all-digital coincidence-detection system implemented in a Field Programmable Gate Array (FPGA) that can cope with the task of generating the high speed trigger for such a camera. The method implemented for coincidence detection is vir tually dead-time free and very fast. It is shown the trigger system can process all the events inside the RPC-PET camera in real-time. This will allow a better understanding of the camera and will contribute to its optimization, simplifying significantly the design of its data acquisition system.